PERAN DEWAN PENGAWAS SYARIAH TERHADAP PENETAPAN MARGIN MURABAHAH PADA PT BANK PEMBIAYAAN RAKYAT SYARIAH SAFIR BENGKULU - Elwardah, Khairiah; Khayati, Mar’atul (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2018)
The many theories of rejection of margin technique in murabahah financing which is considered to be the same as the practice of fixed interest, are the focus of researcher  to answer the concern and problem about their ability as sharia financing product. Sharia supervisory board\ (DPS) as an extension of the DSN-MUI is known to have the duty and function to oversee the implementation of sharia aspects, including overseeing sharia aspects in the use of margin techniques in murabahah financing products. This study aims to determine the working mechanism of the DPS as well as its role in determining the murabahah margin at PT BPRS Safir Bengkulu. This study uses descriptive qualitative research methods. The results of this study reveal that DPS has carried out a working mechanism by playing a role in the establishment of SRB Safir SOPs and periodic supervision of the implementation of BPRS Safir murabahah financing. DPS did not find any practice of irregularities in sharia aspects in the use of margin techniques on murabahah financing products. It's just that the marketing pattern used by BPRS Safir is to attract the interest of prospective debtor customers, it is known that there is a gap in the indication of the practice of fixed interest so that it needs more attention from DPS to be reviewed again.